The effect of oxidized lipids in the diet on serum lipoprotein peroxides in control and diabetic rats. - Staprans, I (1993)
The levels of oxidized serum lipoproteins are increased in humans and animals with diabetes. We have examined the contribution of dietary oxidized lipids on the levels of oxidized lipoproteins. In both control and streptozocin induced diabetic rats, the oxidized lipid content of mesenteric lymph chylomicrons (CM) increased when increasing quantities of oxidized lipids were administered intragastrically. However, at all levels of administered oxidized lipids, the quantity of oxidized lipids in CM was greater in the diabetic animals. These results indicate that oxidized lipids are absorbed and packaged into CM and suggest that there is increased absorption of oxidized lipids in diabetic animals. In nondiabetic rats fed a fat-free diet, the levels of oxidized lipids in their serum lipoproteins were very low. When oxidized lipids were added to the diet, the quantity of peroxides in serum lipoproteins increased about fivefold. In diabetic animals fed a fat-free diet, there were also very low levels of oxidized lipids in their serum lipoproteins, and there was no difference between control and diabetic rats. However, when diabetic animals were fed a diet containing oxidized lipids, the quantity of oxidized lipids in their serum lipoproteins increased 16-fold and were significantly greater than in controls. Thus, in both control and diabetic rats the quantity of oxidized lipids in the diet largely determines the levels of oxidized lipids in circulating lipoproteins. However, in diabetic animals the effect of diet is more pronounced. Together with the CM studies, these results demonstrate that dietary oxidized lipids make a major contribution to the levels of oxidized lipids in circulating lipoproteins and indicate that increased absorption of oxidized lipids in diabetic animals may play a role in the elevation of oxidized lipoproteins observed in this disorder.